Dampak Sustainability Reporting dan Environmental Performance Pada Nilai Perusahaan di SRI-KEHATI - Kamaluddin, Nurhadi; Tri W, Auliya; Fajar ES, Ilham (Magister Ilmu Akuntansi Universitas Jambi, 2024)
This study aims to determine the effect of sustainability report and environmental performance disclosure on company value using SRDI, PROPER, and Tobin's Q measurements. This study is a quantitative study using secondary data obtained from the company's annual report and the company's sustainability reporting report. The population in this study are companies listed on the SRI-KEHATI index for the period 2021-2023. The number of samples used in this study is 54 company data. The data analysis technique used is multiple linear regression analysis with the software used for data processing is SPSS version 26. The results of the study the disclosure of the sustainability report has a significant positive effect on the value of the company. While the disclosure of environmental performance does not have a significant effect on the value of the company.